Let
![\displaystyle f(x) = \sum_(n=2)^\infty \frac{x^n}{n^2(n^2-1) \binom{2n}n}](https://img.qammunity.org/2023/formulas/mathematics/college/n5w05w0q5nhb47ieymjj0dlnytebk6jd7z.png)
Differentiate and multiply by
.
![\displaystyle xf'(x) = \sum_(n=2)^\infty \frac{x^n}{n(n^2-1) \binom{2n}n}](https://img.qammunity.org/2023/formulas/mathematics/college/vjn4m5i9qjba3ppikyu4jd7zzxcls20z8j.png)
Now differentiate twice.
![\displaystyle x f''(x) + f'(x) = \sum_(n=2)^\infty \frac{x^(n-1)}{(n^2-1)\binom{2n}n}](https://img.qammunity.org/2023/formulas/mathematics/college/dmogs6rb0edmtoxhui6gljc436osi0k3or.png)
![\displaystyle xf'''(x) + 2f''(x) = \sum_(n=2)^\infty \frac{x^(n-2)}{(n+1)\binom{2n}n}](https://img.qammunity.org/2023/formulas/mathematics/college/4yxsvt3we4gxyz2eegxwsltyhdm9hgvyp0.png)
Multiply by
.
![\displaystyle x^4 f'''(x) + 2x^3 f''(x) = \sum_(n=2)^\infty \frac{x^(n+1)}{(n+1)\binom{2n}n}](https://img.qammunity.org/2023/formulas/mathematics/college/s8qdpkpeejrdk7ksr61xkneroxtdt88azp.png)
Differentiate one last time and multiply by
.
![\displaystyle x^3 f^((4))(x) + 6x^2 f'''(x) + 6x f''(x) = \sum_(n=2)^\infty \frac{x^(n-1)}{\binom{2n}n}](https://img.qammunity.org/2023/formulas/mathematics/college/y5lr81u2c3cozwa8lnrqn657shw2kdr0pt.png)
Now integrate with the fundamental theorem of calculus, noting that
follows from our series definition. We do this twice and make use of the recurrence
![I_n = \displaystyle \int_0^x y^n f^((n+1))(y) \, dy = x^n f^((n))(x) - n I_(n-1)](https://img.qammunity.org/2023/formulas/mathematics/college/v1cqaqnupd0qei0khku3sn7ytdp15lhxge.png)
Integrating once yields
![\displaystyle x^3 f'''(x) + 3x^2 f''(x) = \sum_(n=2)^\infty \frac{x^n}{n \binom{2n}n}](https://img.qammunity.org/2023/formulas/mathematics/college/sym6asxe7nd4q773mlcvzsbsi0qzcv8ej1.png)
Multiply by
.
![\displaystyle x^2 f'''(x) + 3x f''(x) = \sum_(n=2)^\infty \frac{x^(n-1)}{n \binom{2n}n}](https://img.qammunity.org/2023/formulas/mathematics/college/8uy18ex0p29n9gy1o4pn0phlsk701oyk30.png)
Integrating once more yields the ordinary differential equation
![\displaystyle x^2 f''(x) + x f'(x) - f(x) = \sum_(n=2)^\infty \frac{x^n}{n^2 \binom{2n}n}](https://img.qammunity.org/2023/formulas/mathematics/college/9purvfqoawhoguus9yb1vt62qi8b4syr5t.png)
and we recognize the right side as the series
![\displaystyle \sum_(n=2)^\infty \frac{x^n}{n^2 \binom{2n}n} = 2\arcsin^2\left(\frac{\sqrt x}2\right) - \frac x2](https://img.qammunity.org/2023/formulas/mathematics/college/ya604rqp7c7iuhtewjrx3441kt2caaxvwf.png)
Solving the differential equation is quite doable with the variation of parameters method; we ultimately find
![\displaystyle f(x) = \frac12 + \frac{7x}8 - \left(\frac1x+\frac12\right) \sqrt x √(4-x) \, \arcsin\left(\frac{\sqrt x}2\right) + 2 \left(\frac1x-1\right) \arcsin^2\left(\frac{\sqrt x}2\right)](https://img.qammunity.org/2023/formulas/mathematics/college/fxx3pwuwk5h4cgj38bv8t7llhbs8lpzpqj.png)
Recover the sum we want by letting
. Recall that
![\arcsin(iz) = i \,\mathrm{arsinh}(z) = i\ln(z + √(1+z^2))](https://img.qammunity.org/2023/formulas/mathematics/college/san6lsac55ifa97ayv9pszc2tvw7msr01n.png)
Then we have the following equivalent results involving our old friend
.
![\displaystyle f(-1) = -\frac38 - \frac{\sqrt5}2\, \mathrm{arsinh}\left(\frac12\right) + 4 \,\mathrm{arsinh}^2\left(\frac12\right) \\\\ f(-1) = -\frac38 - \frac{\sqrt5}2 \ln\left(\frac{1+\sqrt5}2\right) + 4 \ln^2\left(\frac{1+\sqrt5}2\right) \\\\ f(-1) = \boxed{-\frac38 - \left(\frac12 - \phi\right) \ln(\phi) + 4 \ln^2(\phi)}](https://img.qammunity.org/2023/formulas/mathematics/college/ulzdoj5nqoub32kwxcefhprl22jchwgnf4.png)